2011
DOI: 10.1371/journal.pone.0026099
|View full text |Cite
|
Sign up to set email alerts
|

Intronic L1 Retrotransposons and Nested Genes Cause Transcriptional Interference by Inducing Intron Retention, Exonization and Cryptic Polyadenylation

Abstract: BackgroundTranscriptional interference has been recently recognized as an unexpectedly complex and mostly negative regulation of genes. Despite a relatively few studies that emerged in recent years, it has been demonstrated that a readthrough transcription derived from one gene can influence the transcription of another overlapping or nested gene. However, the molecular effects resulting from this interaction are largely unknown.Methodology/Principal FindingsUsing in silico chromosome walking, we searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 74 publications
1
46
0
Order By: Relevance
“…L1 insertions may alter targetgene expression levels, 35,57 which are influenced by cell type 44 and the orientations of L1 insertion. 35,58 It is reported that sense insertions are more likely to be disruptive, 35 possibly due to the fact that L1 sense strand contains more cryptic polyadenylation sites than antisense strand.…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
See 2 more Smart Citations
“…L1 insertions may alter targetgene expression levels, 35,57 which are influenced by cell type 44 and the orientations of L1 insertion. 35,58 It is reported that sense insertions are more likely to be disruptive, 35 possibly due to the fact that L1 sense strand contains more cryptic polyadenylation sites than antisense strand.…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
“…35,58 It is reported that sense insertions are more likely to be disruptive, 35 possibly due to the fact that L1 sense strand contains more cryptic polyadenylation sites than antisense strand. 57 Generally speaking, L1 insertions are more likely to suppress than to activate target-gene expression. 35 L1 insertions can contribute to tumorigenesis by inactivating tumor suppressor genes (Figure 2a) or activating oncogenes (Figure 2b).…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that approximately 75% of all known human genes bear Alu sequences within their introns and/or untranslated regions (UTRs) [99] , edited intronic Alu elements may have an impact on the transcript metabolism [98] . Moreover, retrotransposons can influence splicing through exon skipping [100][101][102][103][104][105] , alternative donor or acceptor splice sites [106] , shift of splicing patterns from constitutive to alternative [107] , induction of intron retention and exonization [108][109][110][111] . Second, an outstanding feature of retrotransposons is translational control.…”
Section: R E T R O T R a N S P O S O N S : A W E B O F Sophisticated mentioning
confidence: 99%
“…Specifically, the integration of transposable elements (TEs) can cause mutations that give rise to phenotypic variation among individuals within populations (McClintock, 1950;Wendel and Wessler, 2000), and may generate genetic novelties that contribute to local adaptations (Gonzalez et al, 2010). TEs can also cause insertional knockout of a gene following integration within an open reading frame (Gahan et al, 2001), or decreased splicing efficiency and aberrant polyadenylation when integrated in an intron (Beeman et al, 1996;Kaer et al, 2011). Additionally, integrations within transcriptional regulatory elements (promoters and enhancers) can affect the expression of nearby genes (Chung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%